Analisis Visualisasi Nabi Muhammad dalam Ilustrasi Buku Anak Islami di Indonesia Tahun 2012-2021 - Rasadhika Khansa Amara; Riama Maslan Sihombing (Wimba : Jurnal Komunikasi Visual, 2022)
The development of the visualization of the Prophet Muhammad in Islamic children's illustration books published in Indonesia from 2012 to 2021 is interesting to analyze with various creative solutions from illustrators who continue to apply Islamic law in introducing these important Muslim figures from an early age. The purpose of this study was to identify and analyze by design the development of the visualization of the Prophet Muhammad in Islamic children's illustration books published in Indonesia from 2012 to 2021. The research method used is descriptive, with a qualitative approach. The data collected was analyzed, until finally it can be concluded that all illustrators visualize Him in illustrations of green, yellow, and white light with the word “Muhammad” in Arabic at the center.